Integrating Cultural Heritage and Values through Expressive Arts in the School Curriculum for Personality Development (Malaysian Journal of Learning and Instruction, 2004)
This article is an attempt to heighten the awareness of the general readers, educators as well as professional practitioners to recognize the importance of cultural heritage and values and their contributions to personality development of young children. Children are not born with culture, but rather learn it through enculturation and socialization. Multicultural education is viewed as an intervention and an on-going assessment process to help institutions and individuals become more responsive to the human condition, individual cultural heritage, values and integrity, and cultural pluralism in society. It addresses the aesthetic development of young children, especially in the areas of creativity in music, creative movement, dance, creative dramatics, arts and literature which are proudly acclaimed as parts of our cultural heritage. It focuses to define what is meant by aesthetics and creativity. It further discusses the significant values of our cultural heritage in relation to aesthetic and creative development as well as personality development of the young ones. "Art, when really understood, is the province of every human being. It is simply a question of doing anything well. It is not an outside, extra thing. When the artist is alive in any person, whatever his kind of mind may be, he becomes an inventive, searching, daring, self-expressive creature. He becomes interesting to other people. The world would stagnate without him .... and the world would be beautiful with him ...... He does not have to be a painter or a sculptor to be an artist. He can work in any medium. He simply has to find the gain in the work itself; not outside it. Museums of art will not make a country an art country. But where there is the art spirit, there will be precious works to fill museum". (Robert Henri)